Modification of a method to extract genomic DNA from Aedes aegypti (Diptera: Culicidae) - DE ARMAS R., YAXSIER; RODRÍGUEZ-C., MARÍA M.; BISSET-L., JUAN A. (Revista Colombiana de Entomología, 2005)
The genomic DNA was extracted from 20 Aedes aegypti mosquitoes of the Rockefeller strain. The results from a modified protocol for DNA extraction of mosquitoes were evaluated. The modification of the method consisted in grinding up samples in liquid nitrogen before the extraction of genetic material. The results demonstrated that through the modified protocol genetic material was obtained with higher yield (9.55) and concentration (0.46   g/  l) than the original method. It was corroborated that the resulting DNA was of sufficient quality for RAPD technology and probably other molecular based techniques based on PCR amplification. These results will be used in future genetic studies on Ae. aegypti, the principal vector of dengue.